Viele Wege führen nach Indien - Reorganisation von Arbeit im Zuge der Internationalisierung der IT-Industrie - Feuerstein, Patrick (Universitätsverlag Göttingen, 2012)
Recent developments have caused important changes in the IT industry: while being considered comparatively resistant to international relocation of jobs for a long time, the IT industry's landscape has changed a lot in the course of the 1990s, when IT companies started to make use of low-wage destinations and integrated them in globally distributed workflows. According to many authors the internationalisation of the IT industry does not only put jobs in high-wage countries into jeopardy, but also formalizes and standardizes the working processes, thus significantly limiting the employees´ task discretion. Drawing upon case studies in the Indian subsidiaries of two transnationally operating IT companies, the presented study critically questions this prognosis. The results clearly show that the forms of work organisation and control in the IT industry do not develop homogeneously or uniformly in the course of internationalization. Instead, it is possible to identify specific modes of reorganization that are shaped by varying patterns of internationalization, on the one hand, and the institutional settings of the offshore destinations, on the other hand."